Coping among married and cohabiting individuals in Malaysia during the Covid-19 pandemic: A cross-sectional study on associated factors - Ching Sin Siau; Chua Bee Seok; Mimi Fitriana; Low Wah Yun (Fakulti Psikologi dan Pendidikan, 2021)
After the COVID-19 pandemic outbreak at the end of 2019, families are forced to adapt to various “new norms”. Coping strategy play important role in mediating the relationship between stressors and psychological morbidity. This study aims to examine the predictors of coping among married individuals factoring in the influences of age, gender, educational attainment, socioeconomic status, health and lifestyles. A sample of 221 participants who had a married or cohabiting Malaysian couples involved in this study. The findings indicated that factors such as being older, and male was protecting of coping during the COVID-19 pandemic. A positive appraisal of change after COVID-19 was also protective of better coping, as was better sleep. The results of this study should be used to target interventions on individuals who are in a relationship during the COVID-19 pandemic. The finding enable future studies to perform more rigorous investigations using validated and comprehensive questionnaires to further deepen their understanding on the results of this study.